Off-road consumer: an analysis of the off-road consumption culture - Dalmoro, Marlon (Revista de Administração da UFSM, 2015)
Cultural meanings construction and sharing through consumption activities has been defined as sub-culture of consumption (SCHOUTEN; MCALEXANDER, 1995). With an approach in off-road culture, I seek to understand how consumption mediates the cultural meaning and categories construction associated with 4wheels vehicles and the role of consumption of this type of vehicle in the creation and maintenance of off-road culture. This approach is motivated by the characteristics of culture off-road, which has the 4wheels vehicles as a totemic object. In conducting this study, I got inspiration in the ethnography, with data collection in three different stages of involvement, using observant participation and informal interviews. Results indicate that cultural meanings and categories emerge from the existence of an object viewed by the group as a totem – 4wheels vehicles. The creation and maintenance of off-road culture is resulted of different levels of interaction around the totem. It is understood, therefore, in the analyzed culture, cultural meanings and categories do not emerge from a simple consumption action, but an interaction of different levels (meanings/categories, actors and forms of consumption) around an object considered as a totem by the group.